2001
DOI: 10.1107/s0021889801014728
|View full text |Cite
|
Sign up to set email alerts
|

Rietveld refinements on laboratory energy dispersive X-ray diffraction (EDXD) data

Abstract: Rietveld re®nements of corundum, a rutile and anatase nanocrystalline synthetic mixture, and gypsum, on laboratory energy dispersive X-ray diffraction (EDXD) data are reported. Cell parameters, positional and displacement parameters are in reasonable agreement with single-crystal reference data, despite the rather poor resolution of EDXD data. In particular, good results were obtained for gypsum (unrestrained re®nement) with counting times as short as 1000 s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 27 publications
5
40
1
1
Order By: Relevance
“…The EBSD system was calibrated using a single-crystal silicon standard. The experimental EBSD patterns of the two Ti-dominant oxides were indexed with the structures of synthetic Ti 2 O 3 (Newnham and de Haan, 1962;Rice and Robinson, 1977;Vincent et al, 1980), synthetic Ti 3 O 5 (Onoda, 1998), Sc 2 TiO 5 (Ito, 1971), TiO (Loehman et al, 1969), TiO 2 (anatase, rutile, and brookite) reported in Howard et al (1992), Ballirano and Caminiti (2001), and Meagher and Lager (1979), synthetic Ti 4 O 7 (Marezio and Dernier, 1971), and the newly defined minerals panguite and kangite (Ma et al, , 2013. The HKL software automatically suggests indexing solutions ranked by the lowest "mean angular deviation" (MAD) as an index of "goodness of fit."…”
Section: Methodsmentioning
confidence: 99%
“…The EBSD system was calibrated using a single-crystal silicon standard. The experimental EBSD patterns of the two Ti-dominant oxides were indexed with the structures of synthetic Ti 2 O 3 (Newnham and de Haan, 1962;Rice and Robinson, 1977;Vincent et al, 1980), synthetic Ti 3 O 5 (Onoda, 1998), Sc 2 TiO 5 (Ito, 1971), TiO (Loehman et al, 1969), TiO 2 (anatase, rutile, and brookite) reported in Howard et al (1992), Ballirano and Caminiti (2001), and Meagher and Lager (1979), synthetic Ti 4 O 7 (Marezio and Dernier, 1971), and the newly defined minerals panguite and kangite (Ma et al, , 2013. The HKL software automatically suggests indexing solutions ranked by the lowest "mean angular deviation" (MAD) as an index of "goodness of fit."…”
Section: Methodsmentioning
confidence: 99%
“…10 The structural models for mullite, CoAl 2 O 4 and corundum were based on the data reported in references. [11][12][13] The refinement started in the space group Pbam with mullite structure without cobalt incorporation. 11 For the case of Co 2+ incorporated into mullite, cobalt atoms replaced a fraction of Al atoms at 2a octahedral site.…”
Section: Methodsmentioning
confidence: 99%
“…Several examples of interpretation procedures have been developed in an ad hoc fashion for specific purposes by several authors. In dealing with energy-dispersive diffraction data acquired from a laboratory X-ray source, Ballirano and Caminiti [1] transformed the data to angular dispersive domain for full-pattern refinement. Similarly, Steuwer et al [24] developed an approach involving the transformation of data into a format of time-of-flight neutron diffraction, and used this approach for their strain mapping investigation using energy-dispersive synchrotron XRD.…”
Section: Introductionmentioning
confidence: 99%